Hydrogenase-like electrocatalytic activation and inactivation mechanism by three-dimensional binderless molecular catalyst - Elouarzaki, Kamal (2021)
In response to issues raised by modern energy challenges, molecular electrocatalysis is currently attracting a lot of attention to the tailoring of "model" catalysts, notably understanding the mechanisms and kinetic and thermodynamic parameters that occur during a catalytic reaction. In this regard, nature offers extremely efficient enzymes called hydrogenases. These enzymes that catalyze the reversible interconversions between H₂ and H⁺ at high turnover rates are inactivated by O₂. This inactivation yields odd cyclic voltammetric responses originating from a chemical inactivation-redox activation process (IAP). Although IAP has been extensively studied for hydrogenases, their catalytic mechanism is not fully understood because of the intricate but necessary electrical wiring, desorption, and complex biochemical environment required. Here, we report a unique example of IAP based on a nonenzymatic catalyst prepared by mixing rhodium-porphyrinic catalyst and an interconnected multiwalled carbon nanotubes matrix which presents an excellent and stable electron transfer. We combined organic synthesis, electrochemistry, mathematical models, and density functional theory calculations to uncover the molecular IAP at the catalytic metallic site. We present a mechanistic analysis of the noncatalytic and catalytic responses exhibited by this complex, enabling a comprehensive understanding of the thermodynamic and kinetic parameters that govern the IAP. These stepwise studies support a mechanism for glucose oxidation that proceeds most likely through an EC′CE scheme with catalytic steps similar to the ones reported for NiFe hydrogenases. The overall mechanism of the molecular IAP was detailed on the basis of our experimentally validated models and compared to NiFe hydrogenase IAP. Our findings offer novel perspectives to design finely optimized catalysts by eliminating the inactivation phenomena.